2021
DOI: 10.3390/app11156670
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceuticals in Wastewater Treatment Plants: A Systematic Review on the Substances of Greatest Concern Responsible for the Development of Antimicrobial Resistance

Abstract: In recent years, there is a growing concern about the alarming spread of antimicrobial resistance (AMR) in different environments. Increasingly, many species of bacteria, fungi and viruses are becoming immune to the most commonly used pharmaceuticals. One of the causes of the development of the resistance is the persistence of these drugs, excreted by humans, in municipal and hospital wastewater (WW). Consequently, wastewater treatment plants (WWTPs) are a primary source of antimicrobial resistance genes as no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 51 publications
0
10
0
2
Order By: Relevance
“…The presence of antimicrobials in aquatic ecosystems (Figure 1) is essentially linked to the excretion of unmetabolized antimicrobials by humans and animals [49], direct introduction by aquaculture [50] and inadequate disposal at the hospital level [49].…”
Section: Sources Of Antimicrobials In Aquatic Environmentsmentioning
confidence: 99%
“…The presence of antimicrobials in aquatic ecosystems (Figure 1) is essentially linked to the excretion of unmetabolized antimicrobials by humans and animals [49], direct introduction by aquaculture [50] and inadequate disposal at the hospital level [49].…”
Section: Sources Of Antimicrobials In Aquatic Environmentsmentioning
confidence: 99%
“…Tetracycline (TC) is a broad-spectrum antibiotic with a polycyclic tetraphenyl carboxamide structure that is widely used in livestock and aquaculture, but its extensive use and misuse not only causes cytotoxicity to plants and animals but also leads to the spread of resistance genes and even threatens human health . In recent years, researchers have found different concentrations of TC in domestic sewage and industrial wastewater. , Some studies have reported that the TC content in pharmaceutical wastewater has reached 100–500 mg/L . If the treatment of TC wastewater is not complete, it will lead to an increase in residues in the environment year by year, posing a great threat to human health and the ecological environment .…”
Section: Introductionmentioning
confidence: 99%
“…2 In recent years, researchers have found different concentrations of TC in domestic sewage and industrial wastewater. 3,4 Some studies have reported that the TC content in pharmaceutical wastewater has reached 100−500 mg/L. 5 If the treatment of TC wastewater is not complete, it will lead to an increase in residues in the environment year by year, posing a great threat to human health and the ecological environment.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of One Health, wastewater is an important reservoir of AMR because it contains various AMR from humans, animals, and environments [ 5 ]. The residual antimicrobials in wastewater that are used in humans, animals, and crop plants also are of great concern because they can drive the development and spread of AMR as a result of the selective pressure on bacteria, although the dynamics remain poorly understood [ 6 , 7 , 8 , 9 , 10 ]. A recent metagenomic analysis of ARGs in untreated sewage around the world revealed a higher abundance of ARGs in wastewater in low- and middle-income countries (LMICs) than in high-income countries (HICs), reflecting the state of sanitation and general health [ 11 ].…”
Section: Introductionmentioning
confidence: 99%